1999
DOI: 10.1016/s0022-5223(99)70297-7
|View full text |Cite
|
Sign up to set email alerts
|

Pleural space perfusion with cisplatin in the multimodality treatment of malignant mesothelioma: A feasibility and pharmacokinetic study

Abstract: This multimodality approach is feasible, pharmacokinetically advantageous, and safe enough to undergo further clinical investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
67
1
5

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(78 citation statements)
references
References 23 publications
2
67
1
5
Order By: Relevance
“…With these doses, the systemic drug concentrations never reached the systemic toxic level and were lower than during IPCH (Carry et al, 1993). This difference could be explained by the lower absorption capacity of the pleural membrane and by the enhanced local tissue concentrations after hyperthermic perfusion (Ratto et al, 1999). It may explain the good tolerance of this treatment.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…With these doses, the systemic drug concentrations never reached the systemic toxic level and were lower than during IPCH (Carry et al, 1993). This difference could be explained by the lower absorption capacity of the pleural membrane and by the enhanced local tissue concentrations after hyperthermic perfusion (Ratto et al, 1999). It may explain the good tolerance of this treatment.…”
Section: Discussionmentioning
confidence: 94%
“…Our experience of IPCH shows that the device is safe and reliable for patients with peritoneal carcinomatosis, so we tried this method in the pleural cavity (Gilly et al, 1999). We choose MMC and CDDP because their antitumor effects and intraperitoneal or pleural pharmacokinetics are highly predictable and have been studied most extensively (Rusch et al, 1999;Matsuzaki et al, 1995;Hettinga et al, 1997;Ratto et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Comparisons of three multimodality approaches-PD with normothermic IC, PD with HIOC, and EPP with HIOC-in ten patients with epithelial or mixed, stage I or II, MPM revealed a higher local tissue/ perfusate ratio of platinum concentrations after hyperthermic perfusion than in normothermic perfusion, suggesting a pharmacokinetic advantage imparted by hyperthermia. The safety and feasibility of this approach, as demonstrated through this study, established the benefits of further exploring HIOC as a therapeutic adjunct for MPM (8).…”
Section: Hiocmentioning
confidence: 69%
“…The mechanism by which this occurs is thought to involve protein denaturation which leads to increased membrane permeability, altered cell metabolism, and apoptosis (7). Ratto and colleagues performed one of the first studies investigating the feasibility, safety, and pharmacokinetics of hyperthermic IC using cisplatin (100 mg/m 2 ) (8). Comparisons of three multimodality approaches-PD with normothermic IC, PD with HIOC, and EPP with HIOC-in ten patients with epithelial or mixed, stage I or II, MPM revealed a higher local tissue/ perfusate ratio of platinum concentrations after hyperthermic perfusion than in normothermic perfusion, suggesting a pharmacokinetic advantage imparted by hyperthermia.…”
Section: Hiocmentioning
confidence: 99%
“…Together with chemotherapy agents, hyperthermia is often used to increase the effects of intracavitary therapies; in fact, hyperthermia has a key role in increasing drugs penetration in the tissues and enhance their cytotoxic effects by modifying cells' membrane permeability increasing radiochemo-sensitivity (8). Schaaf et al (9) reported the results of in vitro effects of temperature on tissues during hyperthermic intraperitoneal chemotherapy, confirming that 40 ℃ should be considered the ideal temperature threshold in order to have a benefit in terms of OS and DFI; Ratto et al (8) and Matsuzaki et al (10) confirmed the adjuvant effect of hyperthermia; nevertheless a recent in vitro study (11) questioned its role, stressing the importance of the use of a combination of drugs.…”
Section: Chemotherapeutic Agents and Hyperthermiamentioning
confidence: 91%